The sacred weapon: bow and arrow combat in Iran (Revista de Artes Marciales Asiáticas, 2012)
The following article presents the development of the bow and arrow, and its important role in the history of Iran. The bow always played an important role not only on the battlefield, but also in hunting. It was also considered as a sacred weapon and additionally a royal symbol. Bow and arrow were considered as a superior weapon in comparison with other types of weapons because one could fight with them at a safer distance as one offered by swords, maces and axes. The first part of the article presents a short history of the bow in Iran. Based on historical Persian manuscripts, the next part explains the structure of the composite bow and the materials used for making it. The third part describes some types of bows based on the material, place of production, the usage, and bow type based on the length of the bow and the arrows. The following part talks about different types of arrows based on morphology of arrowheads, the type of plume/feather, the material of the shaft, the material of the arrowhead, the length of arrows, the target of arrows, the place of production of arrowheads and terms for describing its different features of an arrowhead. Then, the article talks about different types of thumb rings, bowstrings, quivers and bow cases and arrow guides for shooting short arrows. The next part discusses different principles of archery as explained in Persian manuscripts. Finally the article describes different archery targets.